OCNDS core features are conserved across variants, with loop-region mutations driving greater symptom burden - Bagatelas, Elena D.; Khan, Maahin Manzoor; Rushing, Gabrielle V. (Frontiers in Human Neuroscience, 2025)
IntroductionOkur-Chung Neurodevelopmental Syndrome (OCNDS) is an ultra-rare genetic disorder caused by de novo mutations in the CSNK2A1 gene, which encodes the catalytic subunit of protein kinase CK2α. OCNDS is characterized by global developmental delay, intellectual disability, speech and language deficits, and other multi-system symptoms. Although prior reports have described considerable phenotypic variability, the relationship between specific CK2α variant locations and symptom presentation remains poorly defined.MethodsWe analyzed natural history data from 48 individuals with pathogenic or likely pathogenic CSNK2A1 missense variants enrolled in Simons Searchlight. Variants were categorized by their location in conserved CK2α protein domains, specifically distinguishing between loop (e.g., glycine-rich loop, p+1 loop) and non-loop regions. We evaluated symptom burden across organ systems, age at diagnosis, and adaptive functioning using caregiver-reported surveys.ResultsAll individuals reported speech/language delay, with additional common features including global developmental delay, neurological symptoms, and gastrointestinal issues. Variants in loop regions were associated with significantly younger age at diagnosis and a higher frequency of hypotonia. Mutations in the glycine-rich loop—known to bind both ATP and the regulatory CK2β subunit—were linked to significantly higher symptom burden and more non-seizure neurological symptoms. No significant differences were observed between variant locations for core features such as sleep issues, intellectual disability, or speech delay..DiscussionOur findings suggest a core OCNDS symptom profile that is conserved across genotypes, with loop-region variants contributing to increased symptom burden. These results reinforce the relevance of conserved functional domains in driving phenotype severity and support the use of mutation location as a potential biomarker to stratify patients for therapeutic prioritization. Further studies incorporating functional assays and larger cohorts are needed to elucidate mechanisms of variant-specific pathogenesis and guide personalized intervention strategies.